2000
DOI: 10.1152/ajplung.2000.278.5.l974
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical strain and dexamethasone selectively increase surfactant protein C and tropoelastin gene expression

Abstract: Physical forces derived from fetal breathing movements and hormones such as glucocorticoids are implicated in regulating fetal lung development. To elucidate whether the different signaling pathways activated by physical and hormonal factors are integrated and coordinated at the cellular and transcriptional levels, organotypic cultures of mixed fetal rat lung cells were subjected to static culture or mechanical strain in the presence and absence of dexamethasone. Tropoelastin and collagen type I were used as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 34 publications
6
62
1
Order By: Relevance
“…Previous in vitro and in vivo studies have shown that phasic alveolar stretch induced by different tidal volumes is an important mediator of LA conversion. In addition, mechanical stretch induces expression of SP-C in fetal lung cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have shown that phasic alveolar stretch induced by different tidal volumes is an important mediator of LA conversion. In addition, mechanical stretch induces expression of SP-C in fetal lung cells (30).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical stresses have been shown to play an important role in regulating various functions of pulmonary epithelial cells such as growth (1)(2)(3), apoptosis (4-7), migration (8,9), surfactant metabolism (1,6,(10)(11)(12), synthesis of extracellular matrix proteins (11,13), and transport of fluids and ions (12,14,15). Disruption of the local mechanical environment of the pulmonary epithelium often elicits abnormal cellular responses and can contribute to the pathogenesis and progression of various respiratory diseases (4,5,(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The pathogenesis of CLD is linked to structural lung immaturity and impaired alveolarization, with elevated levels of disorganized lung elastin (5,15,16). Elastin production is known to be markedly upregulated by strain or stretching of the cell matrix (9,14). Lung histology of infants who have died with CLD shows thickened, tortuous, and irregular distribution of elastic fibers in the walls of distal air spaces, with reduced septation and fewer alveoli (5, 16).…”
mentioning
confidence: 99%